STRATEGI PENGEMBANGAN PRODUK BARU SEBAGAI UPAYA DALAM MENINGKATKAN DAYA SAING PERUSAHAAN (Jurnal Riset Manajemen dan Akuntansi, 2023)
Product development is one of the marketing strategies that aims to increase the company's competitiveness. To realize product development, companies are required to provide a wide range of product choices to consumers by taking into account the dimensions of product development itself. The purpose of this research is to find out how the new product development strategy is an effort to increase the company's competitiveness. the research method used is a literature study of several models adopted and outlined in a descriptive form. The results of this study state that the product development strategy is through a product development process by generating ideas, developing and testing product concepts. Strategies to increase competitiveness include new products for the world, new product lines, improvement of existing products, repositioning, cost reduction.